Extraordinary Legal Remedies By the Prosecutor in Criminal Procedure - Indi Premadasa; Akhmad Khisni (Law Development Journal, 2021)
The purpose of this study is to study and analyze the judicial review of the prosecutors in criminal procedural law. In this paper the author uses the normative juridical method. In the discussion that the public prosecutor has the right to file a basic review of Article 263 paragraph (2) and (3) of the Criminal Procedure Code, apart from Article 263 of the Criminal Procedure Code, the Public Prosecutor has a basis for laws and regulations relating to the issue of reconsideration, namely Article 21 Act No. 14 of 1970 concerning the basic provisions of judicial power, Article 24 of Act No. 48 of 2009 concerning Judicial Power, apart from the statutory regulations mentioned above, the Public Prosecutor filed a Reconsideration on the principles of justice and the principle of balance.